Implementasi Manajemen Kepala SD UMP Dalam Meningkatkan Mutu Pendidikan Islam Tahun Pelajaran 2013/2014 - Muntohar, Muntohar; , Dr. Badaruddin, M.Ag; , Prof. Dr. Bambang Sumardjoko (2015)
Research studies in this is about the implementation of the management of the elementary school is in the education of islam.The objectives to be achieved are the functions described the implementation of the management of the elementary school is in the education of islam.This includes the management planning, organizing, an actuating and controlling the components of it acquired a description of the employees and management the student, management the curriculum, management of infrastructure and financial management. The method used in this research is a descriptive qualitative studies with data collected directly from the field in question are sd ump.Data resources are the primary source of this research is the principal and teachers education of islam.The primary sources a student waka, the deputy head of the curriculum, the deputy head of the infrastructure, the religious activities, the administasi finance and elementary school students and the minimum wage.Data collection includes interviews, in these studies observation, and documentation descriptive qualitative analysis which includes the reduction of data and data, presentation of data and data verification or inference. The result showed that the minimum wage has been implemented elementary school management planning, including its functions organizing, an actuating and controlling improvement in the education of islam.Implementation of headmaster in memanajemen teachers and employees in order to improve the quality of education that with an islamic foundation choose our teacher through several stages, namely the administrative selection a paper test will, keislaman, interviews, and microteaching.Principal does regularly/daily provide motivation, participating in islamic studies workshops, seminar-seminar, mgmp, and training motivation.Implementation of headmaster in memanajemen student to improve the quality of students education selects islam is considering his age pass psychology and skill.Divide the islamic classes to use their names hold the programs keislamana, extracurricular keislaman, and participating in the race.Head of the school curriculum in memanajemen to improve the quality of education in Islam is tasking waka educational curricula and the head of the head. General religious subjects to be combined with keislaman.Implementation of headmaster in memanajemen facilities and infrastructures in order to improve the quality of education in islam is optimally use in religious activity.Implementation of headmaster in memanajemen financial to improve the quality of education is to use to fund islamist activities keislaman.